2019
DOI: 10.1002/jper.19-0432
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive use of enamel matrix derivatives to porcine‐derived xenograft for the treatment of one‐wall intrabony defects: Two‐year longitudinal results of a randomized controlled clinical trial

Abstract: Background The purpose of this study was to evaluate the potential advantages of adjunctive use of enamel matrix protein derivative (EMD) in combination with demineralized porcine bone matrix (DPBM) for the treatment of one‐wall intrabony defects in the molar regions, in comparison with the use of DPBM alone, through a randomized controlled clinical trial. Methods Forty‐two participants were randomly assigned to two groups: one where DPBM with the adjunctive use of EMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 39 publications
4
56
0
Order By: Relevance
“…When the patients of this study were limited to 2- and 3-wall intrabony defects, the baseline PPD was 7.0±1.2 mm and CAL was 7.3±1.1 mm, respectively. In a recent randomized controlled clinical trial, which was only limited to 1-wall intrabony defects, the baseline PPD was reported to be 7.3±0.6 mm and CAL was 7.8±0.6 mm [ 17 ]. When the patients of this study were likewise limited to 1-wall intrabony defects, the baseline PPD was 7.6±0.7 mm and CAL was 8.0±0.8 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the patients of this study were limited to 2- and 3-wall intrabony defects, the baseline PPD was 7.0±1.2 mm and CAL was 7.3±1.1 mm, respectively. In a recent randomized controlled clinical trial, which was only limited to 1-wall intrabony defects, the baseline PPD was reported to be 7.3±0.6 mm and CAL was 7.8±0.6 mm [ 17 ]. When the patients of this study were likewise limited to 1-wall intrabony defects, the baseline PPD was 7.6±0.7 mm and CAL was 8.0±0.8 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…EMD is expected not only to enhance periodontal regeneration through new cementum formation and connective tissue attachment but also to promote soft tissue wound healing and reduce patients' subjective discomfort [ 16 17 22 ]. In an attempt to achieve periodontal regeneration without the adjunctive use of barrier membranes, EMD has become an acceptable treatment option in most periodontal practices [ 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolds used for the regeneration of periodontal tissues can provide a contact guidance that enables timely migration of cells into periodontal defects, followed by promoted regeneration [ 26 ]. To further facilitate cell migration and tissue ingrowth, various bioactive cues including growth factors (GFs) and cytokines have also been delivered with the scaffolds [ [27] , [28] , [29] ]. To our best knowledge, however, there has been no experimental data strongly suggesting scaffold-mediated periodontal healing as fast as GTR.…”
Section: Purpose Of Use Of Biomaterials Scaffolds For Periodontal Regementioning
confidence: 99%
“… [ 27 ] Demineralized porcine bone matrix (DPBM) Enamel matrix derivatives (EMD) Randomized clinical trial; group1: DPBM with EMD, group 2: DPBM only 24 months 42 Although both groups showed clinically and radiographically significant improvement, there were no statistically significant differences between 2 groups. [ 28 ] …”
Section: Clinical Application Of Scaffolds For Periodontal Tissue Regmentioning
confidence: 99%
See 1 more Smart Citation